Export performance of palm oil products in Malaysia / Erien Noor Md Nasir (Faculty of Business and Management, 2007)
This research study investigates the performance and competitiveness of Malaysian palm oil export to the world market especially to major countries in the world such as China and European Union. Both countries are the biggest export market for Malaysian palm oil. There is also overview of world demand of Malaysian palm oil in the world export market most importantly after the implementation of biodiesel as alternative source of energy. This study also acknowledge the great potential of Malaysia to maintain its position as the world leading producers and exporter by producing biodiesel according to the EU standard and accepted worldwide. Researcher has used secondary data or previous study for this research which include government publications, government agencies, statistical analysis, books and periodicals. From the findings, we could see that Malaysia has the advantage of producing and exporting palm oil to the world market since other countries incapable of producing good quality palm oil. Although the volume of palm oil export recorded an increasing trend from 556, 519 tonnes in 2005 to 602, 355 tonnes in the year 2006, the export performance ratio decrease slightly from 92% toward 91% in 2006. This can be said due to several factors such as Malaysian biodiesel blend composition that contain 5% processed palm oil and 95% diesel or B5 does not comply with standard set by European Union that requires a minimum content of 96.5% methyl ester and no more than 0.2% triglycerides. These situations also arise because Indonesia has now beginning to outdo Malaysia in the world export market of palm oil. Based on net export to total trade ratio, we can see that the market share of Malaysian palm oil is twice the share of other commodities export in the world export market.